Application of the Peer Teaching Method to Improve Students' Critical Thinking Skills in Learning the History of Islamic Culture at Madrasah Tsanawiyah Negeri 2 Poso - Asma Waty Samad (al-Afkar, Journal For Islamic Studies, 2024)
The aim of this research is to find out how to improve students' critical thinking skills in learning Islamic Cultural History through the application of the peer teaching method at Madrasah Tsanawiyah Negeri 2 Poso. This research is classroom action research carried out in 2 cycles, namely cycle I and cycle II. This research procedure was carried out in cycles consisting of planning, action, observation and reflection, where each cycle consisted of 2 meetings by using techniques for developing search and problem solving skills on 32 students. The research findings are that students' critical thinking abilities in learning Islamic Cultural History have increased through the application of the peer teaching method. The results of increasing students' critical thinking from cycle I of the first meeting from 50% to 59.37% in cycle I of the second meeting and cycle II of the first meeting from 75% to 90.62% in cycle II of the second meeting, this shows an increase in critical thinking skills in each cycle.